Implementasi Program Arsip Masuk Desa - Burhanudin Dwi Rokhmatun (Khazanah: Jurnal Pengembangan Kearsipan, 2017)
The Village Archives Program (Arsip Masuk Desa/AMD) is a program launched by ANRI since 2009. The objective of AMD Program is to increase the role of archives in administering village government administration in order to improve services to the village community. AMD Program targets are the increasing quality of archival management in village government in accordance with archival rules and legislation.Archival courses presented in the AMD Program includes the Making of Official Scripts, Letters Management, Arrangement and Use of Archives, and Disposal of Archives. The scope that became the object of AMD is the archive created in the Village Government, Village Consultative Board (Badan Permusyawaratan Desa/BPD), and Kelurahan. The obstacles faced in the implementation of the AMD Program stem from the inequalities of potential, conditions, and resources, including village-to-village gaps in the areas of budget and human resources, and socio-cultural differences. Alternative solutions that can be implemented in the implementation of the AMD Program include the formulation of a clear concept, mapping the condition and resources of the village, as well as the preparation of human resources and budget.